3 THE AIR MINISTRY. (July 2022) - Unknown
Abstract : Strachey writes to Londonderry on nationalization and Lloyd George. Thanks for your letter. It was most interesting. I should like to lunch with you next Wednesday very much. You don't say what time so I shall presume 1.30 p.m. as zero, unless you write to the contrary.